PEMBERIAN PIDANA DENDA SEBAGAI PIDANA YANG DAPAT DISUBSIDERKAN DALAM PERKARA TINDAK PIDANA KORUPSI DITINJAU DARI ASPEK TUJUAN PEMIDANAAN (STUDI PUTUSAN NOMOR 57/PID.SUS-TPK/2023/PN KPG) - Yanuarius Maria Gole Duan; Orpa G Manuain; Heryanto Amalo (Petitum Law Journal, 2026)
This study examines the inconsistencies in the application of fines that can be changed to imprisonment in corruption cases, by utilizing the theory of combined punishment that includes retaliation, prevention, and rehabilitation. This study focuses on Decision Number 57/Pid. Sus-TPK/2023/PN Kpg, in which the defendant Bernadus S. Atawolo was sentenced to a fine of fifty million rupiah (Rp 50,000,000), which was changed to a prison sentence of six months. This decision is problematic because it does not reflect the seriousness of the crime of corruption and the losses caused to state finances. Many perpetrators of crimes prefer to serve prison sentences rather than pay fines, which in turn reduces the deterrent effect and damages public trust. Legally, this replacement shows an inconsistency between the general provisions in the Criminal Code and the lack of stricter rules in Law Number 31 of 1999 in conjunction with. Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption. This study suggests the need for reform of the Tipikor Law by eliminating substitute sentences that are too light and replacing them with prison sentences that are commensurate with state losses. Referring to Article 79 of Law Number 1 of 2023 concerning the New Criminal Code, the regulation must ensure that fines cannot be easily avoided and make a significant contribution to asset recovery. This normative legal research applies legal case analysis and statutory interpretation.